Fatigue behaviour of uniplanar CHS gap K-joints under axial and in-plane bending loads - Shao, Yongbo. (2008)
In this study, the stress intensity factors (SIFs) of tubular K-joints have been analyzed using finite element method. The numerical SIF values have been assessed from experimental results. Thereafter, parametric SIF equations and an interpolation method to calculate the SIFs of K-joints under axial loads or in-plane bending loads have been proposed.